Penerapan Algoritma Simpleks dalam Aplikasi Penyelesaian Masalah Program Linier - Chandra, Tintin (STMIK TIME, 2015)
Growth of company to become big company which require manage by professionall. Available resource by nature have boundaries realized by human being as executor of management. In everyday life, many especial decision which faced by a manager company of this Demarcations can cover the limited resource like time, labour, effort, raw material or capital. Many method able to wear for the optimalization of production.One of the method able to be used to finish optimal solution in this problems is method of simplex. There is two way of which can be used to finish problem of this linear program that is by graphical and method of simplex. Graph method suited for finishing linear program which the amount of its variable is equal to two although its variable is equal to three can is also finished by but its graph will very difficult to be read For that, hence selected by method of simplex in solving of the problem of linear program which is its amount of him more than two.Some excess of method of simplex is the amount of variable can more than one, end result more accurate and seen the rest of from existing limitation.